Graﬁczna teza akademicka Andrzeja Kuropatnickiego - Tomczak, Robert T. (Studia Źródłoznawcze. Commentationes, 2017)
Andrzej Kuropatnicki’ academic graphical thesis Graphical academic theses are a very interesting source due to its interdisciplinary nature and the richness of their ideological, political or artistic content. Nevertheless, a majority of “Polish theses” have not been properly examined or analysed by Polish researchers. This is also true for a highly valuable Kuropatnicki’s graphical thesis of 1682, being an apotheosis of King Jan III Sobieski as the victor of Chocim, and Prince Jakub as his successor on the throne, which for a long time had been known only in part. The discovery of the whole original thesis in the National Library in Prague made it possible a thorough and multi-faceted study of the source and to broaden the current knowledge on the subject. Using the hermeneutic approach, philological and comparative methods, together with the literature on the subject of history of arts, it was possible to present the authors of the graphic (the etcher and painter), its inspirer, and also its sophisticated scientiﬁc, ideological, artistic and socio-political context, which led to the printing and propagating of Kuropatnicki’s graphical thesis. In addition, the basic research terminology has been made uniform and some pioneering interpretations put forward. Kuropatnicki’s graphical thesis turned out to be an original and in many aspects innovative ideological and propagandist medium to glorify King Jan III Sobieski and his son in the iconography of the so-called “pre-Vienna epoch”. A prestigious representation of the king in the all’antica type ideally inscribed to both Sobieski’s personal political programme, and the state one, for it explicitly manifested pro-Habsburg and anti-Turkish sentiments in the Commonwealth at that time.